Trevithick Prize - Yiatros, Stylianos (My University, 2026)
Awarded by the Institution of Civil Engineers (UK) for the best article in Proceedings of the ICE Engineering Sustainability Journal in 2007. https://www.icevirtuallibrary.com/page/awards/richard-trevithick-fund-prize
Keywords: Sciences